TRANSLATION ERRORS IN BASIC ENGLISH CONVERSATION VIDEOS FOR CHILDREN ON YOUTUBE - NURLAELA, NURLAELA NURLAELA (English Language Education Study Program, 2024)
This study explores the impact of translation errors in YouTube videos focusing on basic English conversation for children in learning. The research method employed a qualitative approach to analyze translation errors in English conversation practice videos on the LucyMax English channel. By utilizing translation theory, language learning theory, and communication theory, the study aimed to identify and categorize translation errors and their concrete impact on children's second language learning. Data collection involved video transcriptions and translation evaluations to identify possible errors, with qualitative data analysis conducted to develop recommendations for improving the quality of translation in educational videos. The results of the study provide insights into the importance of accurate translations in educational content on YouTube to enhance children's language learning. The findings emphasize the need for content creators to ensure accurate translations align with the learning objectives of second language acquisition for children. This research contributes to the understanding of the impact of translation errors on children's language learning through YouTube videos, highlighting the significance of providing accurate and supportive educational content for effective language acquisition.